2017
DOI: 10.1186/s40635-016-0114-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of intravenous immunoglobulin are mediated through inhibition of complement activation and apoptosis in a rat model of sepsis

Abstract: BackgroundIntravenous (IV) immunoglobulin (Ig) treatment is known to alleviate behavioral deficits and increase survival in the experimentally induced model of sepsis. To delineate the mechanisms by which IVIg treatment prevents neuronal dysfunction, an array of immunological and apoptosis markers was investigated.MethodsSepsis was induced by cecal ligation perforation (CLP) in rats. The animals were divided into five groups: sham, control, CLP + saline, CLP + immunoglobulin G (IgG) (250 mg/kg, iv), and CLP + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Cytokine levels also did not correlate with neuronal loss and Alzheimer-type neurodegeneration markers amyloid β and tau. Thus, our results suggest that cytokines are not directly involved in cognitive dysfunction observed in SIBD patients and cognition is presumably afflicted by altered activation of intracellular pathways that regulate neuronal functions and cell survival by other inflammatory mediators, as demonstrated in animal models of sepsis (17,18). By contrast, IFN-γ levels correlated with S100b, a marker of blood-brain barrier damage suggesting that this cytokine induces leakage of S100b to the peripheral blood, as previously implied (19).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Cytokine levels also did not correlate with neuronal loss and Alzheimer-type neurodegeneration markers amyloid β and tau. Thus, our results suggest that cytokines are not directly involved in cognitive dysfunction observed in SIBD patients and cognition is presumably afflicted by altered activation of intracellular pathways that regulate neuronal functions and cell survival by other inflammatory mediators, as demonstrated in animal models of sepsis (17,18). By contrast, IFN-γ levels correlated with S100b, a marker of blood-brain barrier damage suggesting that this cytokine induces leakage of S100b to the peripheral blood, as previously implied (19).…”
Section: Discussionsupporting
confidence: 66%
“…Geriatric depression scale (GDS) was employed to measure self-rated depressive symptoms in patients. Based on MMSE scores, patients were grouped as those with no cognitive impairment [24][25][26][27][28][29][30], mild cognitive impairment [18][19][20][21][22][23]…”
Section: Assessment Of Neuropsychological Functionsmentioning
confidence: 99%
“…As part of the innate immune response, during a normal infection, MPO is secreted by activated neutrophils, which help in bacterial killing. However, in sepsis, there is an LPS-mediated abnormal hyperproduction of MPO, a potent oxidative enzyme which causes the peroxidation of cell membrane lipids and a decrease in the levels of the antioxidant GSH, leading to tissue dysfunction (24)(25)(26)(27). The present study demonstrated that azithromycin could reverse this imbalance in the oxidant and antioxidant response and potentially minimize tissue injury in sepsis.…”
Section: Fig 10mentioning
confidence: 55%
“…In the present study, we applied both PEEP and RM as OLA. There are several methods to determine optimal PEEP during mechanical ventilation [ 34 , 35 ]. We determined the PEEP level in the OLA group based on the lung mechanics required to maximize lung dynamic compliance [ 36 ].…”
Section: Discussionmentioning
confidence: 99%